Analisis Kompetensi Kepribadian dan Sosial Mahasiswa Pendidikan Biologi di Lampung sebagai Calon Guru Biologi - Saniah, Nikmatus; Hayati, Dwi Kurnia (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Personality and social competencies play a crucial role in building relationships between educators and students. This study aims to describe the personality and social competencies of prospective biology teachers in Lampung Province. The research is descriptive, using a questionnaire as the instrument, which includes indicators of personality and social competencies. Data sources were obtained from respondents, who were 7th-semester biology education students at four higher education institutions in Lampung Province that offer Biology Education programs, namely the Metro Lampung State Islamic Institute, Metro Lampung Muhammadiyah University, Raden Intan Lampung State Islamic University and Lampung University. The results show that the personality competence of biology education students in Lampung as prospective biology teachers is 91% confident and stable, 87% mature, 89% wise, 86% authoritative, and 88% of noble character and able to be role models. The social competence of biology education students in Lampung as prospective biology teachers is 87% skilled in communication, 88% inclusive and objective, 89% sympathetic and empathetic, polite in communication, 87% adaptable to the environment, and 88% able to work well with others. Therefore, it can be concluded that the personal and social competencies of prospective biology teachers in Lampung have reached a good category.